The effect of gamified learning on students’ motivation and vocabulary retention - Dedi Aco; Edi Suwandi (Journal of Research in English Language Teaching and Linguistics, 2025)
This study explores the impact of gamified learning strategies on students’ motivation and vocabulary retention in English as a Foreign Language (EFL) context, an area of increasing importance given the need to enhance engagement and learning outcomes through innovative methods. Recent studies indicate that game elements such as points, badges, and leaderboards can positively influence learner motivation and facilitate vocabulary acquisition. However, the effects of gamification on both motivational and cognitive aspects of language learning, particularly in terms of long-term retention and sustained engagement are still underexplored. The aim of this research is to investigate how gamified instruction affects students’ motivation and vocabulary retention and to analyze the relationship between these two factors. Employing a quasi-experimental design, the study involved 85 intermediate-level EFL learners divided into gamified and non-gamified groups. Data were collected through validated questionnaires assessing motivation a vocabulary tests measuring retention, and post-intervention reflection surveys to capture students’ perceptions of specific gamification elements. Data analysis involved descriptive statistics, independent t-tests to compare group differences, Pearson correlation analyses to explore relationships between motivation and retention, and a multiple regression analysis to explore the impact of game elements. The findings demonstrate that students in the gamified group exhibited significantly higher motivation and better vocabulary retention compared to their counterparts. Moreover, motivation was positively correlated with vocabulary retention, highlighting the importance of engaging instructional strategies. The implications of this study suggest that well-designed gamified learning can serve as an effective pedagogical tool to boost motivation and facilitate long-term vocabulary retention in EFL teaching. Furthermore, the results underscore the need for educators to thoughtfully incorporate game elements and tailor initiatives to learner needs, emphasizing the potential of gamification to transform language education into an engaging, effective process. Future research should explore the long-term effects and broader applicability across diverse educational settings.